A healthy and nuclear family of a patient with inflammatory disease: topical issues and ways of their solution. What can modern medicine offer? - A. M. Lila (Современная ревматология)
The problem of managing reproductive-aged patients (primarily women) with inflammatory diseases is becoming more and more relevant in recent years. It was the objective of the symposium held  during the Annual Scientific and Practical Conference of the V.A.  Nasonova Research Institute of Rheumatology on Early-Stage  Rheumatic Diseases: Scientific Advances and Clinical Practice, at  which leading Russian rheumatologists, gastroenterologists and  gynecologists spoke. The Symposium noted that the current level of  development of medicine allows many reproductive-aged women  suffering from rheumatic diseases, inflammatory bowel diseases,  etc. to well bear and give birth to healthy children. This is achieved  due to the effective control of disease activity, which in turn results  from both the current effective therapeutic tactics and the trusting interaction between the attending physician and the female patient.